Effect of residue and nitrogen management in maize (Zea mays) on mustard (Brassica juncea) productivity and profitability under conservation agriculture - V KADAM, PRAVEEN; JAT, S L; PARIHAR, C M; SINGH, A K; MAHALA, D M; KUMAR, ANUP; RADHESHYAM; NARAGUND, RUXANABI; KUMAR, ARVIND; SINGH, RAJ (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted during 2018–19 and 2019–20 to assess the influence of precision nitrogen management options in preceding maize (Zea mays L.) on succeeding mustard (Brassica juncea L.) under conservation agriculture in sandy loam soil of Delhi. The experiment had two main plots of with residue (WR) and without residue (WoR) retention and four sub-plot treatments of N management applied in maize recommended dose of N (RDN), 33, 50 and 70% basal RDN +green seeker (GS) based N application and uniform recommended dose of 90 kg N/ha was applied for mustard in all treatments. A positive response to residual plus directly applied N and residue application was observed on growth, dry matter accumulation, yield attributes, yield and nutrient uptake of mustard. On a pooled mean basis, crop residue mulching enhanced 7.1 and 8.3% in seed and stalk yield of mustard with 9.4 and 5.2% higher net returns and B:C ratio. The 50% basal RDN + GS guided N applied treatment on pooled basis gave 5.9 and 5.2% higher seed and stalk yield and 7.7 and 7.9% higher net returns and B:C ratio compared to conventional RDN. The highest land productivity in mustard was also obtained with residue retention (`654/day) and 50% RDN +GS (`674/day). Overall, the study concluded that zero tillage with maize residue mulching and recommended nitrogen application in mustard in rotation with 50% basal RDN+GS guided N applied maize improves the crop growth, yield attributes, yield and net returns of mustard, and could be implemented in maize-mustard cropping system under resource-poor semi-arid conditions